2015
DOI: 10.1088/1475-7516/2015/07/011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of He I λ10830 on helium abundance determinations

Abstract: Abstract. Observations of helium and hydrogen emission lines from metal-poor extragalactic H II regions, combined with estimates of metallicity, provide an independent method for determining the primordial helium abundance, Y p . Traditionally, the emission lines employed are in the visible wavelength range, and the number of suitable lines is limited. Furthermore, when using these lines, large systematic uncertainties in helium abundance determinations arise due to the degeneracy of physical parameters, such … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
498
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 427 publications
(553 citation statements)
references
References 69 publications
47
498
7
1
Order By: Relevance
“…Using the Planck CMB observations, 9 the predicted Standard Model abundances of the primordial elements are (68% confidence limits; see Section 5) low-metallicity H II regions in nearby star-forming galaxies. Two analyses of the latest measurements, including an infrared transition that was not previously used, find Y P =0.2551±0.0022 (Izotov et al 2014) and Y P =0.2449±0.0040 (Aver et al 2015). These are mutually inconsistent, presumably due to some underlying difference between the analysis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Planck CMB observations, 9 the predicted Standard Model abundances of the primordial elements are (68% confidence limits; see Section 5) low-metallicity H II regions in nearby star-forming galaxies. Two analyses of the latest measurements, including an infrared transition that was not previously used, find Y P =0.2551±0.0022 (Izotov et al 2014) and Y P =0.2449±0.0040 (Aver et al 2015). These are mutually inconsistent, presumably due to some underlying difference between the analysis methods.…”
Section: Introductionmentioning
confidence: 99%
“…[2] for deuterium and Ref. [3] for helium) and the corresponding predictions based on the standard models of cosmology and particle physics. In fact, in this framework (that we shall refer to as "standard BBN") primordial abundances only depend on the baryon-to-photon ratio η ≡ n b /n γ or, equivalently, on the baryon density ω b ≡ Ω b h 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the extraction of the final helium abundance has been fraught with uncertainties due to correlations among errors in the neutral hydrogen determination and the inferred helium abundance. In 30,31 it was demonstrated that updated emissivities and the neutral hydrogen corrections generally increase the inferred abundance, while the correlated uncertainties increase the uncertainty in the final extracted helium abundance. Therefore, we adopt the value and uncertainty from 31 of Y p = 0.2449 ± 0.0040, (35) which is in general agreement with the predicted value from standard BBN when η 10 is fixed from the Planck analysis.…”
Section: Deuteriummentioning
confidence: 99%